Data Privacy Management, Cryptocurrencies and Blockchain Technology: ESORICS 2021 International Workshops, DPM 2021 and CBT 2021, Darmstadt, Germany, October 8, 2021, Revised Selected Papers - Garcia-Alfaro, Joaquin; Muñoz-Tapia, Jose Luis; Navarro-Arribas, Guillermo; Soriano, Miguel (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed proceedings and revised selected papers from the 16th International Workshop on Data Privacy Management, DPM 2021, and the 5th International Workshop on Cryptocurrencies and Blockchain Technology, CBT 2021, which were held online on October 8, 2021, in conjunction with ESORICS 2021. The workshops were initially planned to take place in Darmstadt, Germany, and changed to an online event due to the COVID-19 pandemic.The DPM 2021 workshop received 25 submissions and accepted 7 full and 3 short papers for publication. These papers were organized in topical sections as follows: Risks and privacy preservation; policies and regulation; privacy and learning.For CBT 2021 6 full papers and 6 short papers were accepted out of 31 submissions. They were organized in topical sections as follows: Mining, consensus and market manipulation; smart contracts and anonymity.